Datawarehouse Sebagai Alat Penunjang Pengambil Keputusan Bisnis dalam Analisis Penjualan: Studi Kasus pada Bagian Penjualan PT XYZ - Sepsugiarto, Sepsugiarto (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Datawarehouse as a business decision support tool for sales data analysis functions to assist the sales department in making daily decisions. PT XYZ often experiences problems in analyzing its sales data, such as can not identify the highest sales areas and the total highest number of sales. The purpose of this study is to analyze and design a decision support tool which is appropriate to the needs of the sales of PT.XYZ. The design of systems uses object-oriented approach while database design uses data warehouse method. Any result obtained from this study is a design a data warehouse that can be used to assist the sales department to create sales decisions everyday. The designed decision-making system based on data warehouse can help the sales department in their daily activities.